Dehydroepiandrosterone (DHEA) supplementation and IVF outcome in poor responders. (3rd April 2017) - Triantafyllidou, Olga; Sigalos, George; Vlahos, Nikos
Abstract: Ovarian stimulation of poor ovarian responders still remains a challenging issue. The incidence of poor responders among infertile women is reported in 9–24% IVF cycles and is associated with very low clinical pregnancy rates. Different treatments have been reported in the literature in an attempt to identify the best stimulation protocol for those patients. Administration of dehydroepiandrosterone acetate (DHEA) was suggested as a promising treatment. It is well known that androgens can influence ovarian follicular growth, augment steroidogenesis, promote follicular recruitment and increase the number of primary and pre-antral follicles. The purpose of this review is to evaluate the effect of DHEA supplementation on women with diminished ovarian reserve. Because of the uncertainty of published data, we suggest that well-designed multicentre RCTs are required to provide more insight on the effectiveness of DHEA. The absence of significant side effects should not be considered as an argument to support DHEA treatment.